Understanding the impact of natural disasters on children within fist hours and days after an event: A phenomenological study through the experience of nurses - Dag, Yeliz Suna; Zengin, Murside; Yayan, Emriye Hilal; Dag, Serhat (Wiley, 2025)
BackgroundChildren are a particularly vulnerable group in natural disasters such as earthquakes, and although they represent a difficult group to research in such situations, there appears to be a lack of literature investigating children's experiences in the immediate post-earthquake period. Experienced nurses can shed light on children's experiences.AimThis study was conducted to examine the experiences of nurses caring for children affected by the earthquake in Kahramanmara & scedil;, Turkey.MethodsThis phenomenological study was conducted with nurses who provided care to children during the Kahramanmara & scedil; earthquake between May and August 2023. The study sample consisted of 14 nurses selected using a purposive sampling technique. Data were collected through in-depth interviews by using the Introductory Information Form and Semi-structured Interview Form developed by the researchers. The interviews were subsequently analyzed using Colaizzi's method.ResultsThe results revealed five themes under two main themes. Under the main theme of nurse, there are subthemes of chaos, helplessness-incompetence, while under the main theme of child, there are subthemes of unresponsiveness, intertwined needs, empathy, and care. The study also highlights the chaotic environment in the immediate aftermath of the earthquake, characterized by a high number of pediatric casualties and psychological trauma, and the nurses' feelings of helplessness as a result of being separated from their families.ConclusionThis study found that nurses caring for children in the earthquake had difficulties in managing children's hospital processes and they demonstrated an empathic approach by trying to communicate with the children in their care. The nurses stated that children should be supported psychologically as well as having their basic needs such as water, food, and shelter met.Implications for nursing and health policyHealth policymakers should be aware that in the early stages of major disasters such as earthquakes, children are not only physically injured but also have basic needs such as water, shelter, and food, and are emotionally affected. It is recommended that disaster management plans be developed to address all children's needs and nurses be provided with psychological support and training to improve their knowledge and skills.
Keywords: Children; disaster management; earthquake; nursing